Innovator Filgrastim versus Generic Filgrastim in Hematopoietic Stem Cell Transplantation Mobilization - Husian, Sadik; Jeyaraman, Preethi; Gupta, S. K.; Rai, Reeta; Pathak, Sangeeta; Dayal, Nitin; Naithani, Rahul (South Asian Journal of Cancer, 2021)
Methods This is a retrospective study. G-CSF was administered in the dose of 10 μg/kg subcutaneous as a single dose for 4 days. On day 5, peripheral blood stem cell (PBSC) apheresis was performed using Haemonetics MCS plus or COBE Spectra apheresis machine through a double-lumen central venous catheter. Primary outcome parameters were the total number of CD34+ HSCs/kg of recipient weight mobilized in peripheral blood and the number of days required for neutrophil and platelets engraftment, respectively.Objective We compared the effectiveness and safety of innovator filgrastim versus generic filgrastim in patients who underwent hematopoietic stem cell transplantation (HSCT).Results A total of 91 stem cell mobilizations was analyzed. There were 58 normal healthy donors for allogeneic HSCT and 33 patients for autologous HSCT. There was no statistically significant difference among groups in terms of total collected CD34+ cells value (p = 0.609). The mean time to neutrophil engraftment was 13.7 days in the innovator group and 13.2 days in the Grafeel group (p = 0.518). The mean time to platelet engraftment was 16.2 days in the innovator group and 14.8 days in the generic group (p = 0.435). The patient who received generic filgrastim had more febrile episodes during the course of transplantation (p = 0.020).Conclusion Generic filgrastim was found to be comparable to original filgrastim for peripheral blood stem cell mobilization in normal healthy donors for allogeneic HSCT and patients for autologous HSCT.
Keywords: bone marrow transplant; CD34; granulocyte colony-stimulating factor; mobilization